AN INVESTIGATION OF TEACHERS’ PEDAGOGICAL SKILLS AND CONTENT KNOWLEDGE IN A CONTENT-BASED INSTRUCTION CONTEXT - Maasum, Tengku Nor Rizan Tengku Mohamad; Maaruf, Nooreiny; Yamat, Hamidah; Zakaria, Effandi (Indonesian Journal of Applied Linguistics, 2012)
Abstract: Advocates of the content-based approach believed that a language can be learnt effectively when it is the medium of instruction rather than just a subject.  Integrating English and content as part of instruction has become one of the cornerstones of second language pedagogy. Researchers claimed that there are many benefits of integrating English and content instruction.  Among the benefits are the increase in students’ interest with content themes, meaningful input and understanding. In 2003, the Malaysian Ministry of Education introduced the teaching and learning of science and mathematics in English for Year One, Form One and Lower Six Form in all government public schools. This paper describes the challenges faced by teachers when they are required to teach content subjects such as science and mathematics in English.  The focus of the paper is on the teachers’ pedagogical skills  and content knowldge which comprises subject matter content, pedagogical approach, classroom management, use of resources, assessment, preparation of teaching materials, managing students, teachers’ compensatory communication strategies, use of first language and teachers’ perspectives of teaching content subjects in English. Data were obtained from a self-report questionnaire administered to 495 secondary school teachers in West Malaysia. Results from the study provide implications for school administrators in making decisions in assignment of  capable teachers to teach the various levels of classes. Suggestions for teacher self-development and life-long learning efforts are also provided.   Key words: Content-based instruction, ESL instruction, second language, first language and second language pedagogy